1993
DOI: 10.1017/s0014479700020640
|View full text |Cite
|
Sign up to set email alerts
|

Lodging in Lentil as Affected by Plant Population, Soil Moisture and Genotype

Abstract: The effects of levels of soil moisture and plant population on lodging and associated losses from mechanical harvesting of two lentil genotypes, one susceptible and one resistant to lodging, were investigated during 1986-87 and 1987-88 at Tel Hadya in northern Syria. High plant population increased lodging because the crowded plants had thin stems, while high levels of soil moisture caused lodging because biological yield was increased. When biological yields were high a two tonne increase in biological yield … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…These findings are supported by previous researchers, namely that lodging is a highly variable trait dependent on environmental conditions (Erskine and Goodrich 1988), and that plant population density may increase lodging (Ibrahim et al 1993). In progenitors to modern lentil cultivars, Whitehead et al (1998a, b) found that modern cultivars were larger plants that contained less lignin compared with their brittle progenitors.…”
Section: Lodging Scoresupporting
confidence: 79%
“…These findings are supported by previous researchers, namely that lodging is a highly variable trait dependent on environmental conditions (Erskine and Goodrich 1988), and that plant population density may increase lodging (Ibrahim et al 1993). In progenitors to modern lentil cultivars, Whitehead et al (1998a, b) found that modern cultivars were larger plants that contained less lignin compared with their brittle progenitors.…”
Section: Lodging Scoresupporting
confidence: 79%
“…The accumulated evidence in different crops has suggested that resistance to lodging is associated with genotype (Ibrahim et al 1993;Pu et al 2000;Inoue et al 2004;Huang et al 2008). Lodging occurs when strong winds are accompanied by rainfall during grain filling stage, which often occurs during the growing seasons for foxtail millet in northern China.…”
mentioning
confidence: 99%
“…Various methods and traits have been used in the field evaluation of lodging in cereal crops (Jezowski 1981;Crook and Ennos 1994;Pu et al 2000;Wang and Du 2001;Berry et al 2003b;Sakata et al 2003), as well as other crops (Ibrahim et al 1993;Huang et al 2008). However, a protocol is not available for screening foxtail millet genotypes resistant to lodging.…”
mentioning
confidence: 99%
“…For the adapted group, CDC Grandora had the widest diameter, which was significantly greater than CDC Plata and CDC Milestone, and finally Crimson Stem diameter was significantly different for plant population treatments, with a decrease in stem diameter as the plant population increased. Board (2001) and Ibrahim et al (1993) reported similar results where stem diameter was found to decrease as plant populations moved from low to high in soybean and lentil, respectively. Thinner stems at high population were associated with increased lodging in both crops.…”
Section: Stem Diameter or Stem Thicknessmentioning
confidence: 77%
“…Ibrahim et al (1993) reported that lodging increased with higher plant populations in lentil. In 2002, no significant differences in lodging due to target plant population were found.…”
Section: Lodgingmentioning
confidence: 99%